Teoría de Dorothea Orem- proceso atención de enfermería aplicado al autocuidado del adulto mayor diabético en el HB-7 Loja - Quinaucho Gutiérrez, Dolores Gabriela (2019)
Self-care is an activity which people do in order to performs their own benefit and maintain their life, it refers to self-monitoring, physical activity, diet, foot check and treatment compliance, among others. The present research work aims to propose an intervention proposal for the diabetic elderly person based on the theory of Dorothea Orem applying the Nursing Care Process with the intervention NANDA, NOC, NIC, a descriptive-transversal study was implemented; a population of 151 elderly patients with diabetes were taken, who attend the area of Internal Medicine of HB-7 Loja. For the data collection process a questionnaire was used with three different contents: sociodemographic, clinical data, and self-care practices, which responded to the proposed objectives. Female gender was found with 52.31%, between the range of 65-70 years old, their illness time was less than one year in 47.68%. There is overweight in a high percentage of the respondents. The self-care practices identified were; Feeding, Physical exercise, Care and cutting of the feet nails, control of glycemia and Frequency of medical controls. From these data it was possible to establish as the main NANDA diagnoses: Nutritional Imbalance, Self-care Deficit, Hygiene, Sedentary, Risk of Level of Glycemia, Therapeutic Breach so that the stages of the PAE were used with the realization of an intervention plan. Finally, a nursing intervention plan was created which was socialized about the self-care practices of the diabetic elderly person. Keywords: Self-care, Elderly adult, Diabetes Mellitus